Hï§awÄlah sebagai Alternatif Pembiayaan Multijasa di Lembaga Keuangan Syariah - Syakur, Ahmad (MUQTASID, 2010)
Islamic banking and other Islamic financing institution need more inovation and to multiply the kind of transaction so that not to stay behind by conventional financing instituon. In the otherhand, hï§awÄlah that we know in the study of fiqh muâÄmalah do not develop optimately in the Islamic economy institution. The application of hï§awÄlah in Islamic banking is little and not popular, whereas by little inovation, hï§awÄlah can be the alternative transaction. This article is an exertion to create the financing concept of multijasa Islamic Banking that more acceptable and more simple by using the hï§awÄlah contract with little inovation. That is the combination between hï§awÄlah bi al-ujrah contract and wakÄlah contract, as the alternative financing for increasing monetary instruments bases the sharia. So the strong and healty financing institution is realized without leaving the sharia. Â  Keywords: multijasa Islamic banking, inovation, hï§awÄlah bi al-ujrah